A novel tool for assessing microbiomes in cultural heritage documents. Issue 1 (November 2020) - Giorgio Righetti, Pier; Zilberstein, Gleb; Zilberstein, Svetlana
Abstract: This mini-review reports a novel way for exploring the world Cultural Heritage, in the absence of damage or contamination of the items under investigation, called the EVA technique. It is based on films of ethylene vinyl acetate (EVA) impregnated with strong anion and cation exchangers and hydrophobic resins, C8 and C18 . When in contact with any surface these films can harvest nano-moles of macromolecules as well as metabolites, which can then be identified by standard instrumentation (e.g. mass spectrometry). Some applications related to microbial contaminations are reported, such as the findings of Koch bacterium in Chekhov's shirt and in a letter by Orwell to a Russian journal editor as well as the Y. pestis and anthrax bacteria in the death registries of Milan's lazaretto in the 1630 plague bout. Novel findings are offered too, such as the identifications of three different strains of Aspergillus in the Aleppo Codex and the detection of melanin (produced by A. niger ) in the Dead Sea Scrolls. It is hoped that the present methodology could open the doors of museums, state archives and private collections for detecting biological traces left by artists, literates and men of culture in their masterpieces.